Theoretical Light in Empirical Darkness: Illuminating Strategic Concealment of Corporate Political Activity - Jia, Nan; Markus, Stanislav; Werner, Timothy (Academy of Management Review, 2023)
Law-abiding firms often attempt to conceal their corporate political activity (CPA), yet the concealment of CPA has not been matched by our understanding of the phenomenon. We develop a theoretical framework consisting of three components to analyze firms’ strategy of CPA concealment. First, we provide a detailed conceptual background on CPA concealment, including what concealment of CPA is and how it can occur. Second, we develop an in-depth analysis of the key benefits and costs of concealing CPA for firms. Finally, we integrate this analysis with positive political theory to place our firm-level calculus in the context of policymaking by identifying the public policymakers whom firms are most likely to influence via CPA concealment. Based on this framework, we generate additional empirically testable propositions on how CPA concealment changes with factors at the country, institution, issue, and firm levels. This study is the first to generate systematic theory on firms’ CPA concealment strategies. Moreover, this research context highlights the particular importance of theory for investigating consequential phenomena that yield scarce data – it is theory which guides data discovery ex ante, helps assess bias ex post, and uncovers key insights that empirical analysis alone cannot generate.